Migration, human rights and governance: Handbook for Parliamentarians N° 24 (2014)
The handbook offers responses to fundamental questions on migration, such as those concerned with its root causes and possible responses in terms of good policies and practices, as well as the challenges, both for migrants and for countries, in relation to national well-being, development and social cohesion. The handbook proposes a balanced approach to make effective laws and policies that address the human rights of migrants and the governance of migration.